Mobilization and Role of Starch, Protein, and Fat Reserves during Seed Germination of Six Wild Grassland Species - Zhao, Ming; Zhang, Hongxiang; Yan, Hong; Qiu, Lu; Baskin, Carol C. (Frontiers in Plant Science, 2018)
Since seed reserves can influence seed germination, the quantitative and qualitative differences in seed reserves may relate to the germination characteristics of species. The purpose of our study was to evaluate the correlation between germination and seed reserves, as well as their mobilization during germination of six grassland species (Chloris virgata, Kochia scoparia, Lespedeza hedysaroides, Astragalus adsurgens, Leonurus artemisia and Dracocephalum moldavica) and compare the results with domesticated species. We measured starch, protein, fat content in dry seeds and the initial absorption of water during imbibition. Starch, soluble protein, fat and soluble sugar content also were determined at five stages during germination. Starch, protein and fat reserves in dry seeds were not significantly correlated with germination percentage and rate (speed), but soluble sugar and soluble protein contents at different germination stages were positively significantly correlated with germination rate for the six species. Starch was mainly used during seed imbibition, and soluble protein was used from the imbibition stage to the highest germination stage. Fat content for all species remained relatively constant throughout germination for six species, regardless of the proportion of other seed reserves in the seeds. Our results for fat utilization differ from those obtained for cultivated grasses and legumes. These results provide new insight on the role of seed reserves as energy resources in germination for wild species.